Community Empowerment Through Increasing Knowledge About the Truth of the Drug NZT-48 as a Neurotrophic in Increasing Brain Potential: Pengabdian Masyarakat Melalui Peningkatan Pengetahuan Tentang Kebenaran Obat NZT-48 sebagai Neurotropik dalam Meningkatkan Potensi Otak - Saristiana, Yuneka; Prasetyawan, Fendy; Mildawati, Ratna; Arifin, Chandra; Rofiq, Abd; Astutik, Widhi (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
The community service aimed to bridge the gap between scientific knowledge and public perception regarding nootropics. Through a comprehensive approach involving meticulous planning, community engagement, educational activities, expert consultations, feedback collection, and evaluation, the program sought to increase awareness and understanding of cognitive enhancement substances among participants. Real-life case studies and guest lectures by renowned experts enriched the learning experience, addressing scientific, ethical, and social perspectives. The proactive involvement of community leaders and an effective awareness campaign ensured high participation and relevance. It underscored the importance of a multidisciplinary approach in addressing complex topics and highlighted the value of engaging communities in meaningful discussions about health and well-being. The program not only educated the community about the realities and myths surrounding NZT-48 and other nootropics but also promoted critical thinking and informed decision- making. By empowering the community with accurate information and fostering a culture of informed skepticism, the program contributed to the betterment of community health and well-being, setting a precedent for future public health education initiatives.